UJI KELAYAKAN ASPEK MEDIA VIDEO MIND MAPPING BERBASIS ETNOSAINS PADA MATERI ZAT ADITIF DAN ZAT ADIKTIF - Asri Widowati; Jumadi Jumadi; Fitria Lafifa; Mirsya Adelia (Jurnal Penelitian Pendidikan IPA, 2023)
This research is a development research with ADDIE development model. ADDIE has five stages of development, including Analysis, Design, Development, Implementation, and Evaluation. However, this research is limited to implementation which aims to determine the feasibility of the developed media and conduct small-scale trials. The Feasibility Test carried out is a validity test and a PA test or Percentage Agreement to reach an agreement between validators. The feasibility test was measured by a questionnaire in 2 aspects, namely the media aspect and the material aspect, each of which was carried out by 4 experts and 1 science teacher from SMPN 3 Bangkalan. Trial and taking responses with a questionnaire, given to students from SMPN 3 Bangkalan. The results of the feasibility test from 2 aspects resulted in an average value of 92% with a very feasible category. The PA test also states that each validator's data has reached an agreement. The response of students after testing the Android-based science flipbook media with the theme of the sensing system resulted in an average value of 89% with a very good response category